2018
DOI: 10.1097/psy.0000000000000516
|View full text |Cite
|
Sign up to set email alerts
|

Everyday Discrimination and Metabolic Syndrome Incidence in a Racially/Ethnically Diverse Sample: Study of Women's Health Across the Nation

Abstract: Everyday discrimination contributes to poorer metabolic health in midlife women in the United States. These findings have clinical implications for the development of MetS and, ultimately, cardiovascular disease and diabetes, and intervention strategies to reduce these outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 39 publications
1
32
0
Order By: Relevance
“…In the U.S., the broad health impacts of racially patterned social stress can be seen not only for non-Hispanic Blacks (Beatty Moody et al, 2018; Chae et al, 2010; Guyll et al, 2001; Lewis et al, 2010; Zahodne, Kraal, Zaheed, et al, 2019), but also for Hispanics (Beatty Moody et al, 2018; Cuevas et al, 2016; Molina et al, 2019), who represent the largest and fastest-growing minority group in the U.S. (Colby & Ortman, 2015). For example, greater racial/ethnic discrimination was associated with psychological distress, unhealthy body mass index, and sleep disturbances in a sample of 1,332 Hispanic adults in the Texas City Stress and Health Study (Garcini et al, 2018).…”
mentioning
confidence: 99%
“…In the U.S., the broad health impacts of racially patterned social stress can be seen not only for non-Hispanic Blacks (Beatty Moody et al, 2018; Chae et al, 2010; Guyll et al, 2001; Lewis et al, 2010; Zahodne, Kraal, Zaheed, et al, 2019), but also for Hispanics (Beatty Moody et al, 2018; Cuevas et al, 2016; Molina et al, 2019), who represent the largest and fastest-growing minority group in the U.S. (Colby & Ortman, 2015). For example, greater racial/ethnic discrimination was associated with psychological distress, unhealthy body mass index, and sleep disturbances in a sample of 1,332 Hispanic adults in the Texas City Stress and Health Study (Garcini et al, 2018).…”
mentioning
confidence: 99%
“…Recent studies using the Everyday Discrimination Scale have found a significant impact of reported discrimination on incident MetS (hazard ratio=1.33) among US women, 33 but only a weak association (OR=1.06) for ethnic groups living in the Netherlands. 34 Racial discrimination is one of many possible forms of unfair treatment, and new research emphasizes the need to consider the joint effects of multiple types of discrimination, both to gauge overall exposure and also to identify loci of unfair treatment rele-vant to prevention.…”
Section: Discussionmentioning
confidence: 97%
“…Transwomen of color may experience particularly high levels of discrimination and adverse health outcomes [ 60 , 62 ]. Discrimination experienced by women of color in midlife is associated with increased risk of hypertension and metabolic syndrome, higher levels of C-reactive protein, a nonspecific marker of inflammation, as well as reduced breast and cervical cancer screening [ 82 84 ]. Given the interconnectedness of social identities, discrimination, and health outcomes, it is particularly important for providers to create space during clinical encounters for patients to share their experiences.…”
Section: Considerations For Discussing Racism With Patients: Intersectionalitymentioning
confidence: 99%